2018
DOI: 10.1177/0095798418780771
|View full text |Cite
|
Sign up to set email alerts
|

Personality, Social Capital, and Depressive Symptomatology Among African Americans

Abstract: The present study examined the relationship between social capital and depressive symptoms and the moderating role of the Big Five personality constructs in a national sample of African American adults. Data were collected from a national probability sample of 803 African American men and women using a telephone survey including measures of the Big Five personality traits, social capital, and depressive symptomatology. Most interestingly, there was evidence for Personality X Social Capital interactions on depr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 59 publications
(103 reference statements)
1
6
0
Order By: Relevance
“…These findings may be particularly relevant for health promotion efforts for African Americans, a group that historically has battled discrimination and health disparities, and has relied on their social network for survival and advancement. Similar to recommendations made by Clark et al (2017) and Clark et al (2018), we suggest that interventions targeting individuals' personality and social skills may help people become more aware of available social support and perceive their support more favorably. Interventions could train participants in increasing and diversifying their social network, teach them how to elicit assistance from their network, provide resources for forming more links with their community, and assist them in learning to accept help when offered (Clark et al, 2017;Wingood et al, 2013).…”
Section: Future Directions Applications and Conclusionsupporting
confidence: 73%
See 1 more Smart Citation
“…These findings may be particularly relevant for health promotion efforts for African Americans, a group that historically has battled discrimination and health disparities, and has relied on their social network for survival and advancement. Similar to recommendations made by Clark et al (2017) and Clark et al (2018), we suggest that interventions targeting individuals' personality and social skills may help people become more aware of available social support and perceive their support more favorably. Interventions could train participants in increasing and diversifying their social network, teach them how to elicit assistance from their network, provide resources for forming more links with their community, and assist them in learning to accept help when offered (Clark et al, 2017;Wingood et al, 2013).…”
Section: Future Directions Applications and Conclusionsupporting
confidence: 73%
“…In addition, the diversity of the social network (Cohen, Doyle, Skoner, Rabin, & Gwaltney, 1997;Eng, Rimm, Fitzmaurice, & Kawachi, 2002), number of social roles, or the amount of social integration (Cohen & Janicki-Deverts, 2009;Crittenden et al, 2014) may be important in the personality-health relationship. Examining social support-related variables (e.g., social and religious capital), including factors such as community participation and interconnectedness, may yield important details about what is most important for mediation, especially in African American samples (Clark, Holt, Wang, Williams, & Schulz, 2017;Clark, Williams, Schulz, Williams, & Holt, 2018). Third, even though we found evidence for social support as a partial mediator for the personality-health relationship, there is further work needed in examining the mediators between social support and health.…”
Section: Future Directions Applications and Conclusionmentioning
confidence: 82%
“…During their longitudinal study in Brazil, Secretti et al [47] found that persons with lower levels of perceived social cohesion had a higher probability of developing a common mental disorder. Others note strong evidence to support that high levels of individual social capital correlate with fewer mental health challenges [45,48,49] and enhanced well-being [9,50]. However, the relationship between social capital and rates of common mental disorders are mixed and in need of further research [45].…”
Section: Social Cohesion and Its Role In Public Healthmentioning
confidence: 99%
“…Another study congruent with our findings reported low social status and social support was significantly related to greater perceived stress, depressive symptoms, and perceived discrimination ( Mama et al, 2016 ). Only one study to date has reported that social capital was related to depression ( Clark et al, 2018 ). Our results reported no significant association between the social capital summary score and depressive symptoms among men in our sample.…”
Section: Discussionmentioning
confidence: 99%
“…Social capital refers to the notion of social growth being cultivated through relationship building ( Boyas et al, 2021 ). Intervention studies investigating or promoting social capital have mostly focused on individual-level change rather than community and multilevel changes, and very few studies focused on Black men ( Clark et al, 2018 ; Dean et al, 2015 ; Ornelas et al, 2009 ). Most of the studies focused on Black men reported the advantages of social capital on health and health behaviors.…”
Section: Introductionmentioning
confidence: 99%